Empiryczne skale ekwiwalentności w pomiarze dobrobytu ekonomicznego rodzin w Polsce - Rusnak, Zofia; Kośny, Marek (Empirical equivalence scale in the measurement of economic welfare of households in Poland, 2005)
One of the consequences of the democratization processes that are taking place in most of the industrialized countries of the world is a growing focus on the socially disabled (e.g. in economical terms) groups. One of the main aims of this work is the attempt to identify some social groups (that could be obtained on the basis of certain analysis) which should be the beneficiaries of the help from the government. The basic tool which is going to be used are so-called equivalence scales - quotients which link income relations with factors not directly connected to income (characteristics of households - e.g. number of people or the age structure of their members). They enable relative comparison of welfare of households of a certain type. Using the equivalence scales we can calculate equivalent incomes or equivalent expenditures. Both of them are used to determine relative levels of incomes required by households of different size and composition to attain comparable standard of living. Author’s aim is to distinguish - on the basis of the results of these scales’ estimation - family groups which require aid. The described attempt to identify the groups of potential beneficiaries of social help will entail methodological study - although very limited - in the first place. Authors will try to indicate - by widely used Engel’s method - what factors may be taken into consideration v'hile estimating the equivalence scales with this method. The second part will involve the analysis of empirical results referring to the comparison of economic situation of different family types. All calculations an comparisons were done using panel data collected by CSO during the Budget household Survey in 2001 year.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1097, s. 109-132